Breast cancer metastasis to the conjunctiva - Bobić Radovanović, Anica Nedeljko; Rašić, Dejan; Buta, Marko; Džodić, Radan (Vojnosanitetski pregled, 2017)
Introduction. Conjunctival metastasis is exceedingly rare, and it is, as a rule, a sign of advanced malignant disease with poor prognosis. We presented a female patient with breast cancer metastasis to the conjunctiva. Case report. A 45-year-old premenopausal female patient was presented with a solitary, yellowish, thin, demarcated lesion in the superior nasal quadrant of the bulbar conjunctiva of the left eye noted by chance a week earlier. There was no sign of irritation, and no pain, and no other functional or morphological problem in either eye or orbit. Five years before the appearance of conjunctival metastasis, breast carcinoma was diagnosed and the patient underwent chemotherapy, preoperative radiotherapy and radical mastectomy. Three years later, computed tomography scan showed metastasis in the left hepatic lobe with ascites and the patient underwent chemotherapy again. But, four months prior to the appearance of conjunctival lesion body scintigraphy showed multifocal sceletal lesions and nuclear magnetic resonance revealed diffuse hepatic metastases and bilateral ovarial tumors. Paliative radiotherapy and hormonal therapy (megestrol, 160 mg) were carried out. An excisional biopsy of the observed conjunctival lesion was performed under topical anesthesia and the material was subjected to histopathological (HP) examination. HP and immunohistochemical examinations established the presence of breast infiltrating lobular carcinoma metastatic to the conjunctiva. The patient showed rapid deterioration after intervention, and died after three weeks. Conclusion. A survival period less than one month after the appearance of conjunctival metastasis deserves attention because it is unexpected and has never been reported previously. It is not a rule that HP presentation of a metastatic lesion is so characteristic that it is possible to determine a primary tumor.